Statistical Modelling of HIV/AIDS in Nepal: A Necessary Enquiry (Nepal Journal of Epidemiology, 2011)
HIV/AIDS surveillance methods evolve over time, so data from the same source may not be directly comparable year to year. The type of data available and the lag-time in availability, may pose challenges to assessing recent impact. Epidemiological measures of HIV/AIDS are numerous and each has important and distinct definitions. Much of the data are estimates only. Focusing on the epidemiology of HIV/AIDS in Nepal, some studies have been published, but nothing has been done in the area of modelling the course of the infection overtime. Given the observed limitations in the current estimation procedures in Nepal, it is better to examine other modelling approaches for HIV/AIDS epidemic (Curve fitting Method) that could be more suitable and give more accurate estimates for the Nepal epidemic scenario.DOI: http://dx.doi.org/10.3126/nje.v1i3.5568 Nepal Journal of Epidemiology 2011;1(3):74-76